Propuesta de mejora para la optimización de almacenes de la empresa del sector automotriz Tauro Servs S. R. L. - Tajara Rodriguez, Juliette Nicole (2023)
This research takes as an example a microenterprise in the automotive sector with problems directly related to its warehouses. Tauro Servs has more than 20 years in the market providing preventive and corrective maintenance services for light, heavy and linear vehicles. The evaluated stores to study contain various products that are used in each service or sold to customers, these products are from different brands such as Toyota, Nissan, Hyundai, Mitsubishi, Mercedes, Land Rover and others. The most notorious problem of the company was the lack of order and cleanliness in the warehouses, which generated delays in the time of service and loss of customers for not having a certain product at the requested time. The objective of the thesis is to develop a proposal for improvement that allows the optimization of the warehouses of the company in the automotive sector. The tools used are the Pareto Curve, Ranking of factors to determine the most representative problem and the Ishikawa Diagram to discover the root cause of the chosen problem. On the other hand, the ABC Matrix, the 5S and the Kaizen philosophy will determine the most appropriate order, organize and maintain the proposed improvement in the long term. As a result, a 10% reduction in costs was obtained in the first year of implementation, after ordering the products according to their rotation it was determined that the most efficient way to work is in order and cultivate a culture of change in its staff.